1979
DOI: 10.1148/131.1.27
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of Perirenal Fat Secondary to Diffuse Retroperitoneal Infiltration

Abstract: Inflammatory effusions and diffuse neoplasia in the fatty retroperitoneal space, which can alter the perirenal fat, can be recognized radiographically because of density differences. The opacity of fluid and tumor accentuates the remaining fat which conforms to the renal contour. This perirenal fatty border appears as a lucent strip when the perirenal fat is not violated and as abnormal perirenal streakiness when the perirenal fat is infiltrated by fluid or tumor. Six cases are described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The integrity of the renal structure and its surrounding tissues is essential for multiple functions, such as forming an effective filtration barrier, maintaining fluid and ion homeostasis ( 12 14 ). A variety of diseases are marked by the involvement of the renal structure and its surrounding tissues ( 6 , 15 17 ). McCort et al reported a sign of the infiltration of perirenal fat by hemorrhage on abdominal CT imaging during renal parenchyma laceration ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The integrity of the renal structure and its surrounding tissues is essential for multiple functions, such as forming an effective filtration barrier, maintaining fluid and ion homeostasis ( 12 14 ). A variety of diseases are marked by the involvement of the renal structure and its surrounding tissues ( 6 , 15 17 ). McCort et al reported a sign of the infiltration of perirenal fat by hemorrhage on abdominal CT imaging during renal parenchyma laceration ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…McCort et al reported a sign of the infiltration of perirenal fat by hemorrhage on abdominal CT imaging during renal parenchyma laceration ( 16 ). Fritzsche et al ( 17 ) reported six cases, such as inflammatory diseases or different tumors, in which perirenal fat was infiltrated by inflammatory fluid and tumor when violated. Anatomically, the renal capsule refers to a thin membranous sheath covering the external surface of the kidney ( 18 ), surrounded by perirenal adipose tissue.…”
Section: Discussionmentioning
confidence: 99%